2022
DOI: 10.26460/md.v6i3.13146
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kewirausahaan, Lingkungan Keluarga Dan Motivasi Terhadap Minat Berwirausaha (Studi Kasus Mahasiswa Manajemen 2018-2021)

Abstract: The purpose of this study was to determine how influential the variables of entrepreneurship education, family environment and motivation on management student'entrepreneurial interest were. The method is a quantitative method. The population and sample in this study were all management students 2018-2022 as many as 128 people. The study resulted in an R coefficient of (0.717) and an Adjusted R Square coefficient of (0.503) this means that there is an influence of entrepreneurship education, family environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research results by Puspitaningsih (2017) and Ritonga et al (2022) prove that learning about entrepreneurship impacts students' willingness to become entrepreneurs through motivational factors. Strengthened by research results by Fathoni (2019), Saragih (2020), Fathiyannida & Erawati (2021), Kardila & Puspitowati (2022) and Febiola et al (2022) simultaneously found that entrepreneurship education through motivation had an impact on students' desire to become entrepreneurs. However, different research results were revealed (Septiawati & Puspitasari, 2023;Yanti, 2019), showing that entrepreneurship education did not influence students' business interests.…”
Section: Introductionmentioning
confidence: 88%
“…Research results by Puspitaningsih (2017) and Ritonga et al (2022) prove that learning about entrepreneurship impacts students' willingness to become entrepreneurs through motivational factors. Strengthened by research results by Fathoni (2019), Saragih (2020), Fathiyannida & Erawati (2021), Kardila & Puspitowati (2022) and Febiola et al (2022) simultaneously found that entrepreneurship education through motivation had an impact on students' desire to become entrepreneurs. However, different research results were revealed (Septiawati & Puspitasari, 2023;Yanti, 2019), showing that entrepreneurship education did not influence students' business interests.…”
Section: Introductionmentioning
confidence: 88%